PENGGUNAAN LKPD BERORIENTASI STRATEGI METAKOGNITIF TERHADAP PENCAPAIAN KOMPETENSI FISIKA PESERTA DIDIK KELAS X - Eka Fitri; Amali Putra; Letmi Dwiridal (PILLAR OF PHYSICS EDUCATION, 2018)
In general, achievement of Physics competence of students in high school is still low. Observations result at SMAN 14 Padang, the causes is the strategy used is not fully centered on the activities of students, and the teaching materials that used have not been able to improve the thinking ability of students. This study aims to determine the Effect of Using LKPD oriented Metacognitive Strategy on Physics achievement of Student’s Competence in X Grade of SMAN 14 Padang. Research carried out included in the type of quasi experimental research (Quasi Experimental Design) with the design of Posttest Only Control Group Design. The study population is all MIPA X grade of SMAN 14 Padang in academic year 2017/2018. Samples were taken using Cluster Random Sampling technique. The research instrument used is a test for knowledge competence, observation format for attitude and skill competence and completed with assessment rubric. Data on the three competencies were analyzed using t test at the real level of 0.05. Based on the result of data analysis, there were significant differences in both sample classes. The result of regression analysis shows that there is strong correlation between LKPD oriented metacognitive strategy to knowledge and skill competence. The result of product moment correlation analysis showed 55% value for knowledge competence and 33.54% for skill competence. So it can be concluded that there is a significant effect on the use of LKPD oriented metacognitive strategies to the achievement of the competence of students in X grade of SMAN 14 Padang.